A MATHEMATICAL MODEL AND PROGRAM OF TREATMENT SUCCESS AND PREDICTION USING REGRESSION ANALYSIS IN MEDICINE (Conference Zone, 2022)
In modern medicine, with the help of computers, it is often necessary to determine the comparative value of the general parameters of the differences between the selected objects that are observed or compared in experimental and clinical research. In solving this task, it is necessary to show clear and concrete values, that is, to determine the characteristic signs of the pathological process, to monitor the dynamic development of the disease, to evaluate the effective traditions of treatment, and others.